2020
DOI: 10.1007/s10064-020-01900-0
|View full text |Cite
|
Sign up to set email alerts
|

Petrophysical and acoustic assessment of carbonate rocks, Zahle area, central Lebanon

Abstract: Transport and acoustic measurements have been conducted on fifteen rock samples collected from central Lebanon to characterize these rock properties and to assess the impact of lithology, pore types, pore sizes, and textural parameters on the storage capacity and elastic characteristics. The spontaneous imbibition of selected samples was examined by detecting the moving capillary front across a sample. The coefficient of capillarity derived from the spontaneous imbibition is positively correlated with permeabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…The measured permeability, porosity, and formation resistivity factor of 316 carbonate rock samples were collected from the reports of Ragland, Verwer et al, Regnet et al, Norbisrath et al, Salah et al, and Tian et al All the samples are either limestone or dolomite with a variety of textures and pore types. This dataset covers a wide range of petrophysical data, with permeability ranging from 0.001 to 25,775 mD, porosity ranging from 0.01 to 0.40, and formation resistivity factor ranging from 6.23 to 5961.84, as shown in Table .…”
Section: Data Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The measured permeability, porosity, and formation resistivity factor of 316 carbonate rock samples were collected from the reports of Ragland, Verwer et al, Regnet et al, Norbisrath et al, Salah et al, and Tian et al All the samples are either limestone or dolomite with a variety of textures and pore types. This dataset covers a wide range of petrophysical data, with permeability ranging from 0.001 to 25,775 mD, porosity ranging from 0.01 to 0.40, and formation resistivity factor ranging from 6.23 to 5961.84, as shown in Table .…”
Section: Data Materialsmentioning
confidence: 99%
“…The NST dataset is further used to verify the accuracy of the F−ϕ correlations in Table 6 and the m−ϕ correlations in Table 7. Since sample ST36A (EQI = 2) in Norbisrath et al 6 and sample M3 (EQI = 2) in Salah et al 36 are not within the range shown in Table 6, they are not considered during verification. As shown in Figure7, the formation resistivity factor and cementation exponent calculated by the EQI method have a good match with the measured values, and the R 2 values are 0.981 and 0.954, respectively.…”
Section: Current Zone Indicatormentioning
confidence: 99%
See 1 more Smart Citation
“…Local geomorphological landforms in Lebanon are influenced by the distribution of the associated physical characteristics of rocks which includes porosity, density, pore type and size, textural parameters, elastic characteristics (Salah et al, 2020). In such a way they mirror lithological structure of the region.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated the influence of microstructures (sedimentary and/or diagenetic), analysed from rock samples, on the acoustic and petrophysical properties of rocks Baechle et al 2008;Brigaud et al 2010;Soete. et al 2015;Reijmer et al 2021) including work on carbonates from central and northern Lebanon (Salah et al 2020a;Salah et al 2020b). Nonetheless, acoustic velocities vary with upscaling in response to different geological heterogeneities .…”
Section: Introductionmentioning
confidence: 99%